KAJIAN KEKOHERENSIAN PARAGRAF DALAM MAKALAH YANG DITULIS MAHASISWA PESERTA MATA KULIAH SEMINAR PRODI PENDIDIKAN BAHASA DAN SASTRA INDONESIA FKIP UNIVERSITAS MUHAMMADIYAH PURWOKERTO - Noorliana, Noorliana; Praptanti, Isnaeni (Sainteks, 2013)
The study was aimed at describing the coherence of paragraphs written by the learners of Seminar Subject of Indonesian Language and Art Study Program – the Teacher Training and Education Faculty – the University of Muhammadiyah Purwokerto. The stated problems covered the quality of paragraph coherence and the factors that influenced the lack of coherence. Method in this study was descriptive quantitative-qualitative, involving the learners’ papers of the seminar subject, i.e the paragraphs available as the data source. The data were gathered through documentation technique, in which quantitative-qualitative analysis was applied; the quantitative analysis technique was used to describe the quality of coherence, whereas the qualitative analysis technique was implemented to describe the influential factors. Result of the study indicated that few paragraphs fell into the grades of ‘good’ and very good’. The finding also concluded that the learners were capable of developing coherent paragraph, though not yet optimum. Keywords: coherension, paragraph.